Case Series: Iatrogenic Penile Amputation Due to Circumcision (Brawijaya Journal of Urology, 2020)
Introduction: Penile amputation is the most common complication of guillotine circumcision. The incidence of penile amputation was highest among males circumcised at 10 years or older There are three cases of iatrogenic penile amputation due to circumcision in Saiful Anwar General Hospital Malang in last 5 years. Case: This series contains three cases of iatrogenic penile amputation due to circumcision in Saiful Anwar General Hospital Malang within 2013-2018 and all of them taken from hospital medical records. One of them already done replantation of penile but unsuccessful due to the preserved of the cutout and the ischemic time of the wound. All of them get injury due to Guillotine technique that performs by the inexperienced people. In cases of a microphallus, buried penis, hypospadias, epispadias, phimosis, and penoscrotal webbing the circumcision should be performed by a surgeon. Conclusion: Guillotine techniques are not safe for patients under 10 years old, because increase the risk of penile injury.